Development of an Audio-Visual-Based Algebra E-Module Oriented Toward Auditory and Visual Learning Styles - Mar'atus Sholehah; M Husen Al Farisy; Astrid Chandra Sari (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
The restricted use of mathematical learning media, which is still dominated by traditional teaching materials and has not been able to accommodate variations in students' learning styles, notably auditory and visual, is the driving force behind this study. This condition makes it difficult for some students to comprehend abstract algebraic content. Thus, the goal of this research is to create a viable audio-visual E-Module that can accommodate both visual and aural learning modalities. Research and development (R&D) using the ADDIE model—which comprises the phases of analysis, design, development, implementation, and evaluation—is the research methodology employed. Expert validators and 38 seventh-grade students from SMP Plus Matholi'ul Anwar participated in the feasibility test as study subjects. Validation sheets and student answer questionnaires with a modified Likert scale were utilized as data gathering methods. According to the study's findings, the created E-Module was deemed legitimate with an average validity score of 3.75. Furthermore, the average score for the feasibility test was 6.51, which is in the extremely practicable range. As a result, the created audio-visual-based E-Module is thought to be suitable for usage as a mathematics learning tool in algebra content and can assist students' comprehension in accordance with their visual and auditory learning preferences.